Testosterone Potentiation of Ionophore and ADP Induced Platelet Aggregation : Relationship to Arachidonic Acid Metabolism - Pilo, R; Aharony, D; Raz, A (Thrombosis and Haemostasis, 1981)
The role of arachidonic acid oxygenated products in human platelet aggregation induced by the ionophore A23187 was investigated. The ionophore produced an increased release of both saturated and unsaturated fatty acids and a concomitant increased formation of TxA2 and other arachidonate products. TxA2 (and possibly other cyclo oxygenase products) appears to have a significant role in ionophore-induced aggregation only when low concentrations (<1 μM) of the ionophore are employed.Testosterone added to rat or human platelet-rich plasma (PRP) was shown previously to potentiate platelet aggregation induced by ADP, adrenaline, collagen and arachidonic acid (1, 2). We show that testosterone also potentiates ionophore induced aggregation in washed platelets and in PRP. This potentiation was dose and time dependent and resulted from increased lipolysis and concomitant generation of TxA2 and other prostaglandin products. The testosterone potentiating effect was abolished by preincubation of the platelets with indomethacin.
Keywords: Arachidonic acid; Platelets; Ionophore A23187; Testosterone